2013
DOI: 10.1371/journal.pone.0076444
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Algicidal Compound from Streptomyces and Algicidal Mechanism to Microcystis aeruginosa

Abstract: The biological control of cyanobacterial harmful algal blooms (cyanoHABs) is important to promote human health, environmental protection, and economic growth. Active algicidal compounds and algicidal mechanisms should be identified and investigated to control cyanoHABs. In this study, the algicidal actinobacterium Streptomyces sp. L74 was isolated from the soil of a nearby pond which located in the center lake of Guanghzou Higher Education Mega Center. Results showed that the algicidal activities of cyanoHABs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 43 publications
3
47
0
Order By: Relevance
“…The sudden collapse in the D. circinale population strongly implicates an external biological effector, such as viral lysis or bacterial predation, neither of which was addressed at length within the scope this study. In this regard, numerous studies have demonstrated biotic mechanisms for the rapid dispersal of cyanobacteria from surface waters that may explain this observation, including phage-induced lysis (Proctor and Fuhrman, 1990;Williamson et al, 2002;Matteson et al, 2011;Steffen et al, 2015), bacteria-induced lysis (Rashidan and Bird, 2001), grazing by protists (Ger et al, 2014), algicidal compounds (Luo et al, 2013; and cyanobacterial programmed cell death (Franklin, 2014).…”
Section: Abioticmentioning
confidence: 99%
“…The sudden collapse in the D. circinale population strongly implicates an external biological effector, such as viral lysis or bacterial predation, neither of which was addressed at length within the scope this study. In this regard, numerous studies have demonstrated biotic mechanisms for the rapid dispersal of cyanobacteria from surface waters that may explain this observation, including phage-induced lysis (Proctor and Fuhrman, 1990;Williamson et al, 2002;Matteson et al, 2011;Steffen et al, 2015), bacteria-induced lysis (Rashidan and Bird, 2001), grazing by protists (Ger et al, 2014), algicidal compounds (Luo et al, 2013; and cyanobacterial programmed cell death (Franklin, 2014).…”
Section: Abioticmentioning
confidence: 99%
“…On the other hand, bacterial quorum-sensing molecules (e.g., acyl homoserine lactones) have been reported to interfere with the germination and growth of Ulva zoospores, a macroalga causing biofouling of artificial constructs [25]. In addition, different taxa of bacteria, for example, Shewanella [26], Streptomyces [27], and Bacillus [28], are known to produce algicidal metabolites. These studies have manifested complex signaling interactions in phycospheres, which we expect to exploit for controlling algae and/or bacteria in the context of biotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, biological agents, including plants [19], protozoan [20], viruses [21] and bacteria [22,23] are considered as effective and biosecure ways to mitigate HABs, and the relationship between bacteria and algae has received particular interest in recent years [24][25][26]. Some bacteria supply cobalamin for algal growth [27], and get nutrients from algae, other bacteria compete with algae for nutrients [28], and some bacteria even produce secondary metabolites with a diverse range of algicidal activities to inhibit or kill algal cells [29]. Therefore, we need to isolate the bacteria with algicidal effect on specific algae, in order to achieve the purpose of effectively solving the problems of HABs.…”
Section: Introductionmentioning
confidence: 99%